Working toward transformation: educational leaders' use of continuous improvement to advance equity - Stosich, Elizabeth Leisy (Frontiers in Education, 2024)
Introduction This comparative case study explores how educational leaders in three networked improvement communities (NICs) situated in the same school district use a continuous improvement (CI) approach, improvement science, to address equity-focused problems of practice. The district that is the focus of this study represents a critical case for understanding educational leaders' use of CI approaches as a lever for equity-focused school reform because the system and state in which it was situated had made ongoing investments in both advancing equity in schools and using various CI approaches. Methods Data collection and analysis focused on interviews with four district leaders and eight school leaders, observations of ~24 h of NIC meetings and planning meetings, and document collection. I draw on sensemaking theory to understand the factors that supported and/or constrained educational leaders' use of CI to advance equity, including more dominant and transformative equity work. Results All educational leaders in the study described and were observed attending to equity as they engaged in CI. The district's sustained investments in equity-focused reform, the use of Plan-Do-Study-Act (PDSA) cycles, data use, and NIC facilitation each acted as important factors that shaped this process. Discussion Advancing equity is long term work that involves addressing deeply rooted beliefs, changing policies and practices, and redesigning systems. Study findings suggest that districts may be more successful in leveraging CI to advance equity when they combine this action-oriented approach with a sustained focus on disrupting oppressive mindsets, values, and beliefs that can hinder transformational change.